The Police Role in Investigating the Crime of Child Murder as a Result of Infidelity Relationships - Nurfita Anggraini Tohari; Sri Endah Arpangi; Arpangi Arpangi (Universitas Islam Sultan Agung, 2021)
This writing aims to identify and analyze the role of the police, criminal investigation mechanisms, obstacles and solutions to the investigation of child murder resulting from adultery. The approach method used is sociological juridical, the writing specification uses descriptive analysis, the source and type of data used are primary and secondary data. Methods of data collection by observation, field research, library research, and using qualitative data analysis methods. The theories used in conducting the analysis are role theory, justice theory, and law enforcement theory. The role of the police has been carried out by the State Police of the Republic of Indonesia as a state apparatus that has the duty to always protect, protect and serve the community in order to achieve security and order. The mechanism for the investigation of the criminal act of murdering the child resulting from an affair starts from the summons of the suspect/witness/expert to the settlement and submission of the case file to the public prosecutor. Obstacles in conducting investigations include constraints on legal substance, constraints on legal structure, and constraints on legal culture. The solution in overcoming these obstacles is coordination between senior investigators and investigators who have just attended investigative training, especially for investigators who have just been appointed as investigators.